Genetic Ancestry using Mitochondrial DNA in patients with Triple‐negative breast cancer (GAMiT study). Issue 1 (1st September 2016) - Rao, Roshni; Rivers, Aeisha; Rahimi, Asal; Wooldridge, Rachel; Rao, Madhu; Leitch, Marilyn; Euhus, David; Haley, Barbara B.
Abstract : BACKGROUND: Triple‐negative breast cancer (TNBC) lacks estrogen, progesterone, and human epidermal growth factor receptor 2 (HER2)/ neu receptors, and is aggressive and therapeutically challenging. Genetic ancestry testing is an emerging medical field. Mitochondrial DNA (mtDNA), which is distinct from nuclear DNA, is maternally inherited and allows for origin determination. Patients with TNBC tend to be younger and are more likely to be African American, making this an ideal disease for mtDNA exploration. To the authors' knowledge, the current study is the first to perform mtDNA for self‐described African American, White, and Hispanic patients with TNBC to identify mtDNA patterns. METHODS: Patients with TNBC who were at any stage of therapy/survivorship were included. Self‐reported ethnicity was confirmed at the time of the prospective buccal swab. Haplogroup prediction was performed on sequencing of hypervariable region 1. Using sequence similarity scores and lineage databases, sequence patterns were determined. Data regarding presentation and treatment, tumor features, and outcomes was collected. RESULTS: A total of 92 patients were included: 31 self‐described African American, 31 White, and 30 Hispanic individuals. Hispanic patients were found to have the largest tumor size (4.5 cm; P  = .01) and youngest age (41 years; P <.0001). Eight patients were BRCA1/2 mutation carriers. There were no differences noted among groups with regard to surgery, lymph node metastases, or survival. Analysis revealed Nigerian, Cameroon, or Sierra Leone ancestry and haplogroups A, U, H, or B to be the most common mtDNA patterns. Twelve discordances (13%) between mtDNA analysis and self‐described ethnicity were identified among the 92 patients. The highest discordance (26%; 8 patients) was noted in self‐described Hispanic patients: 3 had Nigerian ancestry, and 1 individual demonstrated haplogroup K mtDNA (Ashkenazi Jewish ancestry). CONCLUSIONS: Discordance between self‐reported ethnicity and mtDNA analysis was identified in 13% of patients with TNBC. The identification of mtDNA patterns with a predisposition toward TNBC may allow for risk stratification. Cancer 2017;107–113. © 2016 American Cancer Society. Abstract : Genetic ancestry testing is an emerging medical field. Patients with triple‐negative breast cancer tend to be younger and are more likely to be African American, making this an ideal disease for mitochondrial DNA exploration. The results of the current study demonstrate that mitochondrial DNA analysis in patients with triple‐negative breast cancer reveals predominant patterns that may indicate an increased risk of developing aggressive disease.